Promotion of health and human functionality - 10.5020/18061230.2013.p5 - Ana Cristhina de Oliveira Brasil (Universidade de Fortaleza, 2013)
For the development of public health policies in Brazil, two aspects should be taken into consideration, namely, the demographic transition and the epidemiological transition. More and more, it is perceivable an increase in the number of elderly people living with numerous disabilities and also an epidemiological profile. National Household Sample Survey (Pesquisa Nacional por Amostra de Domicílios - PNAD) 1998-2003 indicates a distribution of chronic diseases that, consequently, has generated an expressive number of disabilities. These people with disabilities need health services, and use them when they manage to access them. However, the current models of healthcare for the elderly or people with disabilities are expensive and, in some aspects, are not efficient, requiring preventive strategies and health equipment for the maintenance or recovery of health of an aged population. Thus, the public policy agenda of Brazil should give priority to the maintenance of the functionality of the aged, with monitoring of health status, specific preventive actions on health and education, and care seeking an integral and multidimensional attention, not necessarily focused on disease(1). The need to develop policies and strategies, particularly on health promotion, with a look detached from the disease is justified because health problems come not only from the disease, but from any other circumstance or health condition, such as, pregnancy , aging, stress, genetic predisposition - all classified by D-10, nevertheless, not being able to measure the status alterations related to health, and much less to sort and describe the context in which these problems occur, which complicates and jeopardizes the planning and solvability of actions and services in health, unlike the data by means of qualifiers that the International Classification of Functioning, Disability and Health (ICF) has the potential to generate(2). Brazil is a member country of the World Health Organization, signatory of Resolution WHA54.21-OMS54.21, which recommends the use of the International Classification of Functioning, Disability and Health (ICF), translated into Portuguese in 2003. The main paradigm that ICF brings is the shift from an approach based on the disease to an approach focused on the human functionality (3). Only in May 2012 the National Health Council (Conselho nacioinal de Saúde - CNS) approved the resolution 452 for the Ministry of Health to adopt the ICF, among other uses, as a generator of indicators of human functionality (4). Human functionality, according to the International Classification of Functioning, Disability and Health (ICF) of the World Health Organization, is a comprehensive term that designates the elements of the body, its functions and structures, the human activities and participation in the social processes, indicating the positive aspects of the interaction of individuals with certain health conditions and thee context in which he lives with regard to personal and environmental factors (structural and attitudinal) (3). However, health information appears incomplete, since data regarding the human functionality is not yet meaningful enough to support the developed policies so that they could accomplish the expected results in the face of the disabilities posed by the deficiencies, limitations in activities and restrictions of participation(5). Given the above, a change in direction is required in the paths of public health policies in Brazil, disposing of the exclusively biological approach to the disease, and starting to see it as a problem produced by the society. Therefore, it is necessary to develop information that record not only the disease but the additional aspects of the individuals´ health status. The human functionality is directly influenced both by the presence of diseases, mainly the chronic ones (featuring the change induced by the epidemiologic transition), as by the occurance of negative context, like the diverse environmental barriers, whether they are physical, geographic, technological, legal, among others(5). Such health problems that generated those impairments are harmful not only to the citizens but also to the State, since they burden the social security system (health, welfare and social security), leading to decreased quality of life, especially of those affected by such problems. Despite the finding of facts as the major expenses with medium and high complexity services in health, sickness benefit and early retirements that could have been avoided, one can perceive the lack of specific and properly planned actions, the implementation of which depends on political and administrative will and on a paradigm shift regarding the expanded focus on the etiology of all these health problems. And yet, no public policies are known in Brazil, to follow up, in a transversal and integral way, all the stages of the life cycle or to delineate the profile of functionality and the monitoring of the incidence of disabilities, but also, in particular, actions focused on future generations, based on the expanded concept of health proposed by WHO and defended in the principles and guidelines of SUS. Far more required than simply creating reintegration services is to avoid / prevent social restriction. Therefore, policies must be drawned with a new perspective on the human being, that respects the constitutional principles and guidelines of the NHS and meet the consequences of demographic and epidemiological transitions in order to promote health so that people live without major disabilities an increased life expectancy that has already been settled in Brazil. At the 13th National Conference on Health, the unprecedented proposal n.144 has been approved on Axis II - Public Policies for Health and Quality of Life: SUS in Social Security and the Pact for Health, along with the motion n. 84, aiming to develop and implement a national health functional policy crossing all health policies at their different levels, particularly in areas involving the health of workers, of the elderly, the disabled person, the schoolar, the woman, the man and the other cycles of life, ensuring the interdisciplinary and multidisciplinary performance(6). As from a technical discussion, it is possible to conceive as functional health the status of functionality of individuals and communities welfare at all stages of the life cycle, in activities performance and in social participation, promoting quality of life and autonomy for the full exercise of citizenship. Early detection should be the first step for the actions of functional health, beyond the lines of promotion and care to give visibility to the professional actions of health recovery and prevention of disabilities, seen here in a much broader sense, seeking an outstanding performance of human activities and the most possibly complete participation in society. It becomes evident, then, the need to ensure actions in the promotion of functional health, prevention of structural changes and dysfunctions / disabilities, with or without an underlying disease, and effective recovery of dysfunction, to overcome the limitations and / or restrictions imposed by such condition that affects the functional health. A policy like this brings, among all the advantages of its results, a reduction of damages to social security, arising from these disabilities, as well as an improvement in quality of life, with a low aggregate cost, since the actions require basically the performance of specific professionals, light technology inputs and the utmost possibility of its emphasis on primary care.